2012
DOI: 10.18267/j.pep.427
|View full text |Cite
|
Sign up to set email alerts
|

Gender Wage Gap in the Czech Republic and Central European Countries

Abstract: This paper aims to quantify the basic structure of gender wage gaps in the Czech Republic, Hungary, Poland, and Slovakia, using the EU-SILC 2008 dataset. The structure of the gender wage gap is analyzed based on the Heckman selection model and Oaxaca-Blinder decomposition. The fi ndings are to a great extent similar for the Czech and Slovak Republics. The observed gender wage gap is relatively high in these two countries, compared to Hungary and Poland. A relatively small but positive part of the observed gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 22 publications
(21 reference statements)
3
24
0
14
Order By: Relevance
“…The study is based on cross-sectional data for 2010-2012, which can be found in EU-SILC 2011, 2012and 2013. We selected the data for 25 European countries which contain all the necessary information for our analysis.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The study is based on cross-sectional data for 2010-2012, which can be found in EU-SILC 2011, 2012and 2013. We selected the data for 25 European countries which contain all the necessary information for our analysis.…”
Section: Datamentioning
confidence: 99%
“…The remainder of the gender wage differences remains unexplained. Studies also show that the raw gender pay gap and its unexplained part varies among countries (for example, Christofides et al, 2013;Plantenga et al, 2006;Mysíková, 2012;Hedija, 2015). The causes of gender wage differences and differences among countries continue to be an economic mystery.…”
Section: Introductionmentioning
confidence: 99%
“…Zmínit lze například studie zaměřené na Českou republiku a na diskriminaci na trhu práce (Nešporová, 2015), na důsledky problémů sladění práce s péčí o rodinu (Dudová, Hašková, 2014), horizontální segregaci (Valentová et al, 2007), genderovou rovnováhu v oblasti odměňování (Vlachová, 2014;Mysíková, 2012;Pytlíková, 2012) a vertikální segregaci (Křečková, 2013;Křečková Kroupová, 2009). …”
Section: Situace žEn V čEské Republiceunclassified
“…Veľká pozornosť je venovaná aj problematike miezd ako jedného z druhov príjmov, pričom autori sa zaoberajú témami ako štatistické modelovanie miezd (Marek, 2010;Bílková, 2012Bílková, , 2013Bartošová a Longford, 2014), hľadanie faktorov determinujúcich výšku miezd (Gottvald a Rievajová, 2013), príp. špecifi cký dôraz je kladený na faktory jedného percenta najvyšších miezd (Pacáková, Linda a Sipková, 2012), vzťahy medzi priemernými mzdami a produktivitou práce (Zdeněk a Střeleček, 2012), rodový rozmer odmeňovania (Mysíková, 2012). Rozdeľovanie príjmov je v úzkom vzťahu k chudobe a slovenskí a českí autori sa v období niekoľkých posledných rokov zaoberali napr.…”
Section: Východiská Zdroje úDajov a Použité Metódyunclassified